ON π-EXTENSIONS OF THE SEMIGROUP Z_+ - Grigoryan, T.A.; Lipacheva, E.V.; Tepoyan, V.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the paper inverse π-extensions of the semigroup Z_+ are studied. It is shown that π-extension of the semigroup Z_+ is inverse, if and only if its π-extension coincides with p(Z_+). The existence of a non-inverse π-extension for any abelian semigroup is proved.